2017
DOI: 10.21206/rbas.v7i2.352
|View full text |Cite
|
Sign up to set email alerts
|

Utilização De Sensor Portátil Para Recomendação De Adubação Nitrogenada Associada Ao Uso De Fungicidas Em Arroz Irrigado

Abstract: O objetivo do trabalho foi determinar a influência da presença ou ausência da aplicação de fungicidas, e dos manejos de nitrogênio, com base no uso do clorofilômetro e de acordo com a recomendação local, naprodutividade de grãos e nas características agronômicas das cultivares BRS Tropical e Epagri 109 de arroz irrigado, em várzea tropical. A pesquisa foi conduzida em um Gleissolo Háplico distrófico de várzea,por dois anos consecutivos. O delineamento experimental usado foi o de blocos casualizados, com quatro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In this study, we found N sufficiency indices (NSI) below 95%, indicating, therefore, the time of greatest need for N application, which is similar to the results obtained by Santos et al (2011Santos et al ( , 2017 and Carvalho et al (2018), who verified the need for N application at the V3 -V4 and V7 -V8 stages of rice growth.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In this study, we found N sufficiency indices (NSI) below 95%, indicating, therefore, the time of greatest need for N application, which is similar to the results obtained by Santos et al (2011Santos et al ( , 2017 and Carvalho et al (2018), who verified the need for N application at the V3 -V4 and V7 -V8 stages of rice growth.…”
Section: Resultssupporting
confidence: 91%
“…Maximum N agronomic efficiencies were 56 and 65 kg of grain produced per kg of N applied, which was obtained with 30 kg ha -1 of N as first and second topdressing, and 55 kg grain obtained with up to 90 kg of total N applied. Santos et al (2017) and Carvalho et al (2018) obtained higher N use efficiencies in irrigated rice with nitrogen Rev. Ceres, Viçosa, v. 66, n.6, p. 422-430, nov/dec, 2019 fertilizer applied according to chlorophyll meter readings than with N applied according to the local recommendation, which is based on pre-fixed times.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation